The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19116581
|View full text |Cite
|
Sign up to set email alerts
|

Megaproject Environmentally Responsible Behavior in China: A Test of the Theory of Planned Behavior

Abstract: Construction megaprojects play a significant role in today’s infrastructure provision in terms of sustainable development, and their increasing proliferation worldwide means the environmentally responsible behavior (ERB) of those involved are becoming of vital importance. This study investigates how ERB can be best supported in megaprojects by first identifying the motivational factors that are involved based on the theory of planned behavior (TPB), followed by a survey of 188 managers involved in China megapr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 97 publications
(142 reference statements)
1
6
0
Order By: Relevance
“…Subjective norms had no significant effect on intention to adopt green construction in this study. However, while the results affirm the outcomes of previous studies such as Swarnaet al(2022) and Jain et al (2020) showed that subjective norms had no effect on intention to implement sustainable practices, the results contradict the findings of Xie et al (2022) who submitted that subjective norms had the strongest effect on the intention to adopt environmentally responsible behaviour.…”
Section: Discussion Of the Findingssupporting
confidence: 57%
See 1 more Smart Citation
“…Subjective norms had no significant effect on intention to adopt green construction in this study. However, while the results affirm the outcomes of previous studies such as Swarnaet al(2022) and Jain et al (2020) showed that subjective norms had no effect on intention to implement sustainable practices, the results contradict the findings of Xie et al (2022) who submitted that subjective norms had the strongest effect on the intention to adopt environmentally responsible behaviour.…”
Section: Discussion Of the Findingssupporting
confidence: 57%
“…(2022) and Jain et al . (2020) showed that subjective norms had no effect on intention to implement sustainable practices, the results contradict the findings of Xie et al . (2022) who submitted that subjective norms had the strongest effect on the intention to adopt environmentally responsible behaviour.…”
Section: Data Analyses and Findingsmentioning
confidence: 79%
“…Researches have shown that subjective norms and behavioral attitude have high explanatory power for individual environmentally responsible behavior (Chi et al, 2023;Qiu et al, 2022;Xie et al, 2022). Based on TPB and previous empirical findings, we hypothesized the following.…”
Section: Organism-responsementioning
confidence: 94%
“…Researches have shown that subjective norms and behavioral attitude have high explanatory power for individual environmentally responsible behavior (Chi et al, 2023; Qiu et al, 2022; Xie et al, 2022). Based on TPB and previous empirical findings, we hypothesized the following.H1 Subjective norms have a positive impact on environmentally responsible behavior.H2 Behavioral attitude has a positive impact on environmentally responsible behavior.…”
Section: Theoretical Hypothesesmentioning
confidence: 99%
“…According to recent academic discourse, social responsibility behaviors in megaprojects manifest in varied forms, including contractual social responsibility behaviors [27], megaproject citizenship behaviors [28], environmental responsibility behaviors [14,29,30], and greenwashing behaviors [31][32][33]. Contemporary studies of these behaviors fall into two primary categories: research focusing on the motivation behind MSR behaviors [3,5,29,30,34,35] and research examining the effects of MSR behaviors [2,[10][11][12]14], which encompass outcomes related to project sustainability, organizational performance, and industry performance. Specifically, within the framework of global sustainable development, expectations regarding the value of megaprojects have surged, with MSR increasingly serving as a barometer for a project's "value" [36].…”
Section: Msrb and Project Performancementioning
confidence: 99%